Estimation of Dose-Rate Effectiveness Factor for Malignant Tumor Mortality: Joint Analysis of Mouse Data Exposed to Chronic and Acute Radiation - Doi, Kazutaka; Kai, Michiaki; Suzuki, Keiji; Imaoka, Tatsuhiko; Sasatani, Megumi; Tanaka, Satoshi; Yamada, Yutaka; Kakinuma, Shizuko (Radiation research, 2020)
Uncertainties due to confounding factors in epidemiological studies have limited our knowledge of the effects of low-dose-rate chronic exposure on human health. Animal experiments, wherein each subject is considered to be nearly identical, can complement the limitations of epidemiological studies. Therefore, we conducted a joint analysis of previously published cancer mortality data in B6C3F1 female mice chronically and acutely irradiated with 137Cs γ rays to estimate the dose-rate effectiveness factor. In the chronically irradiated animal experiment conducted by the Institute for Environmental Sciences, mice received irradiation at dose rates of 0.05, 1.1 or 21 mGy per day for 400 days from 8 weeks of age. For the acutely irradiated animal experiment conducted by the National Institute of Radiological Sciences, mice received irradiation at 35, 105, 240 or 365 days of age with 1.9, 3.8 or 5.9 Gy at a dose rate of 0.98 Gy per min. Because the preliminary analyses suggested that the risk was dependent on the age at exposure, a model was applied that considered risk differences depending on this factor. The model analysis revealed a three-fold, significantly decreased risk per Gy in mice exposed to 21 mGy per day compared to that in acutely irradiated mice. This resulted in a dose-rate effectiveness factor larger than that reported previously.